Respuesta :
4x – 5y = –18 (1st)
3x + 2y = –2 (2nd)
Multiply 1st equation by 2 and 2nd equation by 5
4x – 5y = –18 (1st) (mul. 2)
3x + 2y = –2 (2nd) (mul. 5)
8x - 10y = - 36
15x + 10y = - 10
-----------------------add
23x = - 46
x = -2
3x + 2y = –2
3(-2) + 2y = –2
-6 + 2y = -2
2y = 4
y = 2
(-2,2)
answer
(–2, 2)
3x + 2y = –2 (2nd)
Multiply 1st equation by 2 and 2nd equation by 5
4x – 5y = –18 (1st) (mul. 2)
3x + 2y = –2 (2nd) (mul. 5)
8x - 10y = - 36
15x + 10y = - 10
-----------------------add
23x = - 46
x = -2
3x + 2y = –2
3(-2) + 2y = –2
-6 + 2y = -2
2y = 4
y = 2
(-2,2)
answer
(–2, 2)
Answer:
Step-by-step explanation:
Solve by the linear combination method.
4x – 5y = –18
3x + 2y = –2
i selected the incorrect answer and the correct answer is bellow.
Selected Answer:
Incorrect
(–2, 7)
Correct Answer:
Correct
(–2, 2)